ANALISIS WACANA KRITIS PADA KONTEN “MASJID UNTUK SEMUA” DI MEDIA YOUTUBE CISFORM UIN SUNAN KALIJAGA, YOGYAKARTA - Muhammad Irpan Nur (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
CISForm (Center for the Study of Islam and Sosial Transformation) is an institution that takes a role in the production of content on Youtube. By seeing how much content has been uploaded, this research examines the value contained in the content of CISForm. In this case, this research focusses on one content; namely "Masjid untuk Semua." This study uses qualitative research methods and is dissected with critical discourse analysis by Norman Fairclough. Analysis is reviewed in three dimensions, namely text analysis, discourse practice, and sociocultural practice. The results of this study indicate the existence of discourse construction games in the video. Text analysis shows the number of a clause and phrase games in each conversation. Text discourse wants to eliminate Islam that is labeled as cruel, intolerant, ill-tempered, scornful, disrespectful and does not respect different beliefs. The level of discourse practice shows that CISForm tends to produce content related to sosial phenomena. Educational background and the organization and thoughts of the figures in the CISForm institution are part of the birth of the discourse construction factor in the video. Sociocultural practice, answers the problem of the noise that carries the name of religion. The concept of rahmatan lil ‘alamin is a concept that colours the content of the video "Masjid untuk Semua," this concept emphasizes mutual respect even though different in belief. Muslim relations with tolerant non-muslims is constructed in the "Masjid untuk Semua" content.Keywords:  Discourse, Masjid untuk Semua, non-muslim, YouTube, CISForm UIN SUKA.